2013
DOI: 10.4103/0970-9290.118000
|View full text |Cite
|
Sign up to set email alerts
|

Detection of putative periodontopathic bacteria in type 1 diabetic and healthy children: A comparative study

Abstract: Statistical significance was not observed for the prevalence of periodontopathic bacteria in type 1 diabetic subjects. The results of the present study thus reveal the absence of risk of periodontitis by these bacterial species in type 1 diabetic subjects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…Barring our earlier study, hardly there are any previous reports correlating T1DM and periodontitis with regard to the prevalence of periodontal bacterial pathogens [12]. The aim of the present study was to compare the prevalence and assess the risk of four other key periodontopathic bacteria viz., Eikenella corrodens , Campylobacter rectus , Prevotella intermedia and Prevotella nigrescens among the type 1 diabetic children and healthy children/adolescents between the age group of 7 and 14 years, using polymerase chain reaction.…”
Section: Introductionmentioning
confidence: 73%
“…Barring our earlier study, hardly there are any previous reports correlating T1DM and periodontitis with regard to the prevalence of periodontal bacterial pathogens [12]. The aim of the present study was to compare the prevalence and assess the risk of four other key periodontopathic bacteria viz., Eikenella corrodens , Campylobacter rectus , Prevotella intermedia and Prevotella nigrescens among the type 1 diabetic children and healthy children/adolescents between the age group of 7 and 14 years, using polymerase chain reaction.…”
Section: Introductionmentioning
confidence: 73%
“…Other studies found no significant difference in the prevalence of putative periodontopathic bacteria between T1DM and healthy children, challenging the notion of an increased risk of periodontitis associated with specific bacterial species in T1DM subjects (Arangannal et al, 2013). Similarly, Lalla et al (2015), suggested similar subgingival infection patterns between individuals with T1DM and healthy controls, particularly under controlled periodontal disease severity conditions (Lalla et al, 2015).…”
Section: Type 1 Diabetes Mellitus and Oral Microbiotamentioning
confidence: 98%